圆带传动在植球机基板传送系统的应用与研究 - 王鹤; 郭俭; 石洋 (Jixie chuandong)
In order to prevent static electricity for ball mounter substrate transmission,the round belt transmission is designed.The round belt transmission comprises motor,pulleys,bound belt and so on.The axial force and the moment of round belt transmission are analyzed,suitable motor and bound belt are chosen through calculation and analysis,which makes the round belt transmission apply to various sizes of substrates.Finally,the commissioning and operation of substrate transfer system is carried out.The results indicate that round belts transmission can realize transmission of substrate transfer system steadily and improve mounting quality of ball mounter.